Debt relief under the HIPC initiative: Context and outlook for debt sustainability and resource flows - Lisandro Abrego; Doris C. Ross (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper analyses debt relief efforts by creditors to alleviate the debt burden of lowincome countries. The Heavily Indebted Poor Countries (HIPC) Initiative builds on traditional debt relief, and for the first time involves relief on multilateral debt. It seeks to reduce debt to sustainable levels and eliminate any debt overhang that might hinder growth and investment. It provides substantial debt relief to eligible countries by reducing their overall debt stocks by about one-half, or, together with traditional relief over time, by some 80 percent. It lowers debt service payments of HIPCs substantially, provides room for increased social spending, and provides a solid basis for debt sustainability. The latter requires efforts by both debtors and creditors. To find poverty reduction efforts, HIPC relief is important, but much broader international support is needed as external transfers to HIPCs in the past far exceeded debt service paid. Experience has shown that external support can only be effective if it reinforces sound policies implemented by HIPCs themselves. Thus debt relief and ODA are most important not in isolation, but as help for self-help.
Keywords: F34; F35; O11; O19; 330; debt relief; external debt sustainability; HIPC Initiative; poverty reduction; Auslandsverschuldung; Internationale Kreditvergabe; Schuldenerlass; Armut; Low-Income Countries